Introduction to marine cargo management - Rowbotham, J. Mark (Lloyd's practical shipping guides, 2014)
This unique text provides a clear and comprehensive introduction to the principal elements involved in the management of marine cargo and the carriage of goods by sea. Not only does it analyse key theories and debates in the maritime freight sector, it is equally instructive on practice and logistics. Furthermore, the book provides a thorough guide to the roles and responsibilities of all parties involved in this dynamic industry.